Development of a chip-on-tape encapsulation process - Mui, Yew Cheong. (2009)
This thesis summarizes the work conducted in an effort to develop an encapsulation process for a chip-on-tape package. The various studies conducted included encapsulation material selection, encapsulation process studies and optimization and FEA simulations for the prediction of package performance. Reliability tests which included temperature cycle test and high temperature- high humidity test were also conducted in the material selection phase.